114 Minima timings of ultra-short orbital period eclipsing binaries - Loukaidou, G.; Gazeas, K. (Information Bulletin on Variable Stars, 2018)
We present 114 times of minima of 6 ultra-short orbital period eclipsing binaries.
Keywords: CCD photometry